2021
DOI: 10.1007/s10530-021-02471-1
|View full text |Cite
|
Sign up to set email alerts
|

Undaria pinnatifida exudates trigger shifts in seawater chemistry and microbial communities from Atlantic Patagonian coasts

Abstract: The invasive kelp Undaria pinnatifida has spread from northeastern Asia to temperate coastal environments worldwide, with profound effects on colonized ecosystems. In this work, we analyzed the effect of exudates from U. pinnatifida on the chemical and microbial properties of seawater from a semienclosed gulf from Atlantic Patagonia. Exudates of U. pinnatifida, consisting mainly of carbohydrates, were released at a rate of 1.6 ± 0.8 mg C g -1 algae day -1 , affecting the quality and optical properties of seawa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 92 publications
(119 reference statements)
0
3
0
Order By: Relevance
“…Notably, Flavobacteria were predominant at T8, a period of rapid DOC degradation. Studies have demonstrated that Flavobacteria is a member of a rich marine microbial community that is speci cally responsible for the metabolism of algal carbohydrates and plays a key role in the biodegradation of macroalgae-derived complex organic matter through the action of extracellular enzymes (Lozada et al 2021;Mann et al 2013). Ruegeria was observed to increase in relative abundance during the slow DOC decline period to become the dominant genus in this period.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Flavobacteria were predominant at T8, a period of rapid DOC degradation. Studies have demonstrated that Flavobacteria is a member of a rich marine microbial community that is speci cally responsible for the metabolism of algal carbohydrates and plays a key role in the biodegradation of macroalgae-derived complex organic matter through the action of extracellular enzymes (Lozada et al 2021;Mann et al 2013). Ruegeria was observed to increase in relative abundance during the slow DOC decline period to become the dominant genus in this period.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of speciation and toxicity of Cu in marine macroalgae has been reviewed by Gledhill et al (1997). Marine brown macroalgae are known to release extracellular organic matter, such as humic material, polyphenolic material, and sulfonated polysaccharides (Dogs et al, 2017;Lozada et al, 2021). Schramm (1993) found that organic substances exuded by Fucus vesiculosus and Laminaria saccharina decreased Cu toxicity, thus exhibiting the potential to alter the toxicity of Cu or its bioavailability.…”
Section: Exudation: Complexing Ligandsmentioning
confidence: 99%
“…Members of this superphylum are particularly abundant in the marine environment, where they are proposed to play key ecological roles, such as in global nutrient cycling [5][6][7]. They have also been found associated with brown algae within their epiphytic biofilms [8][9][10], where algae exudates may influence the microbial community structure [10,11]. Despite the limited information on the metabolic potential of members of the PVC superphylum, recent studies have suggested that this group includes many members specialized in the degradation of sulfated polysaccharides synthesized by macroalgae [4,12,13].…”
Section: Introductionmentioning
confidence: 99%